Crosstalk analysis of silicon-on-insulator nanowire-arrayed waveguide grating - 李凯丽 安俊明 张家顺 王玥 王亮亮 李建光 吴远大 尹小杰 胡雄伟 (Chinese physics B, 2016)
The factors influencing the crosstalk of silicon-on-insulator （SO1） nanowire arrayed waveguide grating （AWG） are analyzed using the transfer function method. The analysis shows that wider and thicker arrayed waveguides, outsider fracture of arrayed waveguide, and larger channel space, could mitigate the deterioration of crosstalk. The SOI nanowire AWGs with different arrayed waveguide widths are fabricated by using deep ultraviolet lithography （DUV） and inductively coupled plasma etching （ICP） technology. The measurement results show that the crosstalk performance is improved by about 7 dB through adopting 800 nm arrayed waveguide width.